Lactation Counseling Improves Success of Breastfeeding - Sri Sat Titi Hamranani; Devi Permatasari; Fitriana Noor Khayati (GLOBAL HEALTH SCIENCE GROUP, 2023)
Breast milk is the ideal food for growing newborns, as many components of breast milk serve as a source of nutrition for growth and as the first line of defense against infection. Mothers often fail to breastfeed or stop breastfeeding earlier than necessary. The problems faced by mothers in the hospital show that low milk production in the first few days after giving birth is an obstacle to breastfeeding their babies. The many reasons for mothers not to breastfeed their babies prove that lactation counseling needs to be given to mothers, especially during the post partum period. Objective:This study aims to determine the effect of lactation counseling on breastfeeding success in the Siti Hajar Room, RSU Islam Klaten. Method: The design of this research is pre-experimental with one group pretest-posttest design. The sampling technique used purposive sampling. The sample used was 21 respondents. The data collection instrument used the LATCH questionnaire. Statistical test using wilcoxon. Results: The results showed that the characteristics of the respondents in this study were an average age of 25.10 ± 3.223 years, most of them had higher education (52.4%), worked (66.7%) and all respondents were primiparas (100%). Breastfeeding success before counseling averaged 6.19 ± 1.327 and after counseling averaged 9.00 ± 0.775 with an average increase of 2.81 while the p value was 0.000; α = 0.05. Conclusions: The conclusion of this study is that lactation counseling increases breastfeeding success.